2020
DOI: 10.2106/jbjs.20.00775
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Orthopaedic and Trauma Service

Abstract: The purpose of this form is to provide readers of your manuscript with information about your other interests that could influence how they receive and understand your work. The form is designed to be completed electronically and stored electronically. It contains programming that allows appropriate data display. Each author should submit a separate form and is responsible for the accuracy and completeness of the submitted information. The form is in six parts. Identifying information. The work under considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
163
3
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(199 citation statements)
references
References 4 publications
12
163
3
6
Order By: Relevance
“…Regarding surgical volume and nature of surgery performed during the COVID-19 period, an almost complete disruption of elective surgery was reported, and only 5.4% of the trainees responded that all routine activities and surgery continued as usual, while more than half (57.1%) stated that only emergency procedures were performed. This is in accordance with other studies reporting a dramatic decline in elective surgery [8,21,22]. In a survey of members of the European Hip Society (EHS) and the European Knee Associates (EKA), 68.4% of surgeons responded that elective inpatient procedures were no longer being performed, and 68% reported that all outpatient procedures were cancelled, while only 0.7% reported no changes at their department [8].…”
Section: Discussionsupporting
confidence: 88%
“…Regarding surgical volume and nature of surgery performed during the COVID-19 period, an almost complete disruption of elective surgery was reported, and only 5.4% of the trainees responded that all routine activities and surgery continued as usual, while more than half (57.1%) stated that only emergency procedures were performed. This is in accordance with other studies reporting a dramatic decline in elective surgery [8,21,22]. In a survey of members of the European Hip Society (EHS) and the European Knee Associates (EKA), 68.4% of surgeons responded that elective inpatient procedures were no longer being performed, and 68% reported that all outpatient procedures were cancelled, while only 0.7% reported no changes at their department [8].…”
Section: Discussionsupporting
confidence: 88%
“…Christey et al identified a virtually identical 43% reduction in all injury-related admissions to a New Zealand Major Trauma Service when they compared two-week periods sandwiching the introduction of lockdown measures in New Zealand [18] . This reduction has been explained in other reports as an indirect effect of lockdown measures because, if people are at home, not surprisingly, the number of workplace accidents and traffic accidents should decline, as well as the risk of fractures, since most falls occur outdoors [ 10 , 17 , 18 ]. One potential reason that we observed an even greater pre- to post- lockdown reduction in patient presentations (from 2213 patients between February 16 th and March 15 th to just 450 between March 16 th and April 15 th , a 79.9% reduction) than they observed in the US and New Zealand might relate to our institution's status as a national referral center for patients with suspected or confirmed COVID-19 during the pandemic [6] .…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, many strategies have been proposed and implemented, worldwide and in Peru, in an attempt to contain this pandemic, some of them more successful than others [7] , [8] , [9] . To date, considerable information has been published on the impact of the COVID-19 outbreak, including the orthopedic field, in Asia, North America and Europe [10] , [11] , [12] , [13] , [14] , [15] , [16] . However, little is yet known about the impact of the COVID-19 outbreak in Latin America.…”
Section: Introductionmentioning
confidence: 99%
“…They also pointed out a number of reasons for changes in behavior of patients to delay or not opt for medical attention such as fear of contracting COVID-19, altruistic consideration for health-care workers, financial constraints, or preference for private health-care facilities. 26 Stoker et al also showed decrease in orthopaedic trauma events in Michigan due to the pandemic and shelter-inplace order. 28 He suggested that decrease in traffic volume and road traffic accidents in the same time in Michigan could have caused the decrease in trauma volume.…”
Section: Discussionmentioning
confidence: 96%
“…25 Wong et al revealed the reduction in orthopaedic activity in 43 public hospitals and 122 outpatient clinics in HongKong due to pandemic. 26 They showed almost 70 -90% reduction in elective procedure due to administrative measures to decrease the elective cases owing to around 60% reduction on elective hospital admission. However such measures allowed for conservation of PPE, reduction of unnecessary hospital traffic, and preservation of staffing to afford deployment to COVID-19 wards.…”
Section: Discussionmentioning
confidence: 99%